Elementary classical Greek - Williams, Frederick (Southern Illinois University Press ; Eurospan, 2004)
"Elementary Classical Greek stresses a clear and orderly presentation of the language, accompanied by individual sentences or short passages that illustrate grammar, give practice in reading, and help build vocabulary. Drawing on decades of experience teaching classical Greek, Frederick Williams presents a text in which grammatical explanations are clear and succinct and the selected readings are varied, interesting, and useful. Included in the nearly one hundred reading passages are excerpts from Plato's Ion and Republic, Aristophanes' Clouds, and Paul's First Letter to the Corinthians." "The popular textbook is designed for a course meeting for two semesters. There are twenty-four lessons in all, with appendixes on prepositions, Greek numbers, and the Greek verb, plus Greek-English and English-Greek vocabularies, a grammatical index of subjects, and a list of Greek authors cited. Selected readings are presented first in simple, then more complex, language until the reader is led to the actual words of the ancient author - all within the same lesson. This elementary device helps bridge many of the difficult gaps between modern English and ancient Greek."--BOOK JACKET.